2020
DOI: 10.3390/rs12020319
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Various Spectral Indices on Land Cover Change Detection Using Change Vector Analysis: A Case Study of Crete Island, Greece

Abstract: The main objective of this study was to explore the impact of various spectral indices on the performance of change vector analysis (CVA) for detecting the land cover changes on the island of Crete, Greece, between the last two decades (1999–2009 and 2009–2019). A set of such indices, namely, normalized difference vegetation index (NDVI), soil adjusted vegetation index (SAVI), albedo, bare soil index (BSI), tasseled cap greenness (TCG), and tasseled cap brightness (TCB), representing both the vegetation and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The NDVI is often used for the mapping of changes in land cover [50,51] and, according to Singh et al [52], this index, used in the LULC classification, produces a significant improvement in classification accuracy. The BSI is mainly used to highlight the difference between agricultural and non-agricultural land thanks to its enhanced ability in identifying bare soil and fallow lands [53]. These additional indices are commonly used to improve the LULC classification.…”
Section: Dataset Compositionmentioning
confidence: 99%
“…The NDVI is often used for the mapping of changes in land cover [50,51] and, according to Singh et al [52], this index, used in the LULC classification, produces a significant improvement in classification accuracy. The BSI is mainly used to highlight the difference between agricultural and non-agricultural land thanks to its enhanced ability in identifying bare soil and fallow lands [53]. These additional indices are commonly used to improve the LULC classification.…”
Section: Dataset Compositionmentioning
confidence: 99%
“…On the other hand, according to the relative results by an administrative perspective, Chania prefecture was found to be most prone in erosion (Figure 9). The increasing amount of rainfall water from east to west as a result of rainfall's spatial variability [58] could be considered the main natural driving force.…”
Section: Discussionmentioning
confidence: 99%
“…The cloud mask was removed and the empty pixels were fulfilled by the values of cloud-free images of directly previous or next months. Afterwards, the Normalized Difference Vegetation Index (NDVI) was calculated in the ArcGIS environment by the following Equation [58]:…”
Section: Implementation Of Ruslementioning
confidence: 99%
“…Recent findings have indicated that the region's precipitation regime facilitates rainfall induced soil erosivity to a larger extend than was previously thought [26,27]. From a hydrogeological perspective, the island is mainly composed of pre-alpine and alpine carbonate formations and neogene and quaternary (alluvial) sediments which expedite water penetration; hence, the region exhibits limited surface water resources [28]. Crete is a well-studied region in the context of climate change impacts, mainly for its location and size, its environmental heterogeneity, but also due to its hydrological isolation from continental Greece, which makes it ideal for studying climate change impacts [21,[29][30][31].…”
Section: Case Study Regionmentioning
confidence: 96%